2013
DOI: 10.3384/lic.diva-98242
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Behaviour of Austenitic Alloys

Abstract: Room: ACAS, Linköping UniversityCover: Dynamic recrystallization in AISI 316L slow strain rate tensile tested at elevated temperature.Printed by: LiU-Tryck, Linköping, Sweden, 2013 ISBN 978-91-7519-512-4 ISSN 0280-7971 Distributed by: Linköping University Department of Management and Engineering SE-581 83, Linköping, Sweden © 2013 Mattias CalmungerThis document was prepared with L A T E X, October 2, 2013 AbstractThe global increase in energy consumption and the global warming from greenhouse gas emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…3,4 To enable the use of ECCI and EBSD, which are surface sensitive techniques, specimens have to be carefully prepered. 5 Dynamic strain ageing (DSA) may occur in these alloys and is characterized by serrated yielding during plastic deformation. The serrated yielding comes from pinning and unpinning of dislocations by solute interstitials and substitutional atoms, at lower and higher temperatures respectivly, denoted Portevin-Le Châtelier (PLC) effect.…”
mentioning
confidence: 99%
“…3,4 To enable the use of ECCI and EBSD, which are surface sensitive techniques, specimens have to be carefully prepered. 5 Dynamic strain ageing (DSA) may occur in these alloys and is characterized by serrated yielding during plastic deformation. The serrated yielding comes from pinning and unpinning of dislocations by solute interstitials and substitutional atoms, at lower and higher temperatures respectivly, denoted Portevin-Le Châtelier (PLC) effect.…”
mentioning
confidence: 99%
“…At elevated temperature serrated yielding, also called jerky flow, can be seen in the stress-strain curve giving support for the existence of dynamic strain ageing (DSA) [9,10]. Earlier studies [11,12] have shown that AISI 316L has decreasing ductility and strength with increasing temperature when using a strain rate of 2x10 -3 /s in the temperature regime where DSA are active. DSA could be responsible for giving a contribution to the lower ductility at elevated temperatures when using a higher strain rate (2*10 -3 /s) [13].…”
Section: Resultsmentioning
confidence: 87%
“…AISI 304 shows less serrated yielding at the low strain rate at 700°C than for a higher straining rate. For aged samples of Alloy 617 serrated yielding is not present at 700°C using a strain rate of 2*10 -3 /s, but DSA occur in the stress-strain curve for the non-aged sample under same conditions [7]. However, the serrated yielding occurs when using a strain rate of 10 -6 /s at 700°C, probably due to a decrease in dislocation motion rate.…”
Section: Resultsmentioning
confidence: 94%